Representasi “Alpha Female” di Dalam Konten Video “Kick Andy - Gita Savitri dan Paul Mantap Memilih Childfree atau Hidup Tidak Punya Anak” - Rizky Kurniadi; Delvie Nellaety; Syarifah Parameswara Basuki (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
This study attempts to describe and analyze the representation of Alpha Female in a feminist perspective. Alpha Female is described as a strong, independent, and confident woman, who puts herself in a dominant position and dares to take initiative in her life. However, the representation of Alpha Female in the media often creates debate among feminist activists as well as the public.. This study discusses and observes the concept of alpha female representation in a feminist perspective in a YouTube video titled "Kick Andy - Gita Savitri and Paul Steadfast in choosing childfree or living without children" describes how Gita Savitri as Alpha Female is represented in the media, and evaluates its impact on her role in public. Gita Savitri is an Indonesian female activist who has become an icon of Childfree Feminism in Indonesia and has become an inspiration for many women in Indonesia to pursue careers and choose not to have children, despite social and cultural pressures that still think women must have children to be considered perfect. This study uses a constructivism paradigm with a qualitative approach using multimodality research strategies. The method used is focus group discussion (FGD) which is a data collection technique, generally carried out in qualitative research with the aim of finding the meaning of a theme according to the understanding of a group with purposive sampling subjects with the participants age range from 25 to 27 years old.